Determinants of Anemia and Its Impact on the Academic Performance of Female Students at Senior High School 1 Rote Barat Daya - Bessie, Ayu Puspita Suryani; Oematan, Grouse; Liufeto, Mega (Jurnal Pangan Gizi dan Kesehatan, 2025)
Background: Anemia is a condition where the hemoglobin (Hb) level in the blood is lower than normal. Anemia can cause fatigue, decreased concentration, which can affect learning achievement. Objectives: This study aims to determine the factors that influence anemia status and its effect on learning achievement of female students of SMA Negeri 1 Rote Barat Daya. Methods: The type of research used is descriptive analytic research with a cross sectional approach. The population in this study were female students in grades 11 and 12 of SMA Negeri 1 Rote Barat Daya as many as 402 people. Data analysis used in this study was simple logistic regression and multiple logistic regression. Results:  statistical tests with simple logistic regression showed that there was a relationship between nutritional intake and diet to anemia status with a value of (ρ-value=0,000). However, there was no relationship between history of illness and anemia status (ρ-value=0,936) and no relationship between anemia status and learning achievement (ρ-value=0,247). The results of the analysis using multiple logistic regression showed that there was an influence between diet and anemia status (95%CI value = 1,656-158,389); there was an influence between nutritional intake and anemia status (95%CI value = 2,075-69,601). Conclusions: that schools should often hold socialization about the causes and symptoms of anemia, as well as its impact on health, especially for female students. Female students should avoid the habit of consuming foods or drinks containing caffeine or tea in large quantities, because it can inhibit iron absorption.